Review of surgical techniques and guide for decision making in the treatment of benign parotid tumors - Psychogios, Georgios; Bohr, Christopher; Constantinidis, Jannis; Canis, Martin; Vander Poorten, Vincent; Plzak, Jan; Knopf, Andreas; Betz, Christian; Guntinas-Lichius, Orlando; Zenk, Johannes (European archives of oto-rhino-laryngology, 2021)
PURPOSE: Surgical treatment of benign parotid tumors has developed in the direction of less invasive procedures in recent years and has raised great debate about the best surgical approach. Aim of this article is to analyse anatomical and other factors that are important in selection of the appropriate surgical technique in treatment of benign parotid tumors. Furthermore, to discuss the risk of complications and recurrent disease according to selected operation. Finally, to define patient selection criteria to facilitate decision making in parotid surgery and become a guide for younger surgeons. METHODS: Literature review and authors' personal opinions based on their surgical experience. RESULTS: All possible surgical techniques for benign parotid surgery with advantages and disadvantages are being described. An algorithm with anatomical and other criteria influencing decision making in benign parotid surgery is presented. CONCLUSION: Surgeons nowadays have many options to choose from for benign parotid surgery. ECD is one of the many surgical techniques available in parotid surgery and can achieve excellent results with proper training and if used for proper indications. PSP is mainly indicated in large tumors of the caudal part of the PG (ESGS level II). SP represents a universal solution in parotid surgery and should be the first technique young surgeons learn. TP has only few but important indications in benign parotid surgery. Surgeons need to carefully consider the patient and his/her preoperative imaging as well as her or his own special expertise to select the most appropriate surgical technique.
Keywords: Parotid Neoplasms; Parotid surgery; Female; pleomorfní adenom; Surgical techniques; Decision Making; ženské pohlaví; Extracapsular dissection; lidé; pooperační komplikace; retrospektivní studie; Adenoma, Pleomorphic; Male; Postoperative Complications; nádory příušní žlázy; rozhodování; Pleomorphic adenoma; mužské pohlaví; Partial superficial parotidectomy; Retrospective Studies; Parotid Gland; parotis; Humans